The role of ADAM8 in the mechanophenotype of MDA-MB-231 breast cancer cells in 3D extracellular matrices - Hayn, Alexander; Fischer, Tony; Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2023)
The majority of investigations of cancer cells have been performed in an 2D environment. Here, we hypothesize that the bidirectional interplay between breast cancer cells and their microenvironment is critical for the outcome of the disease. Thereby, the tissue remodeling processes evoked by cancer cells are important for cancer cell-driven mechanical probing of their matrix environment and on cancer cell adhesion and motility. When remodeling processes have been explored, the emphasis was placed on matrix metalloproteinases and rather not on a disintegrin and metalloproteases (ADAMs). However, the role of ADAM8 in cell mechanics regulating cellular motility in 3D collagen matrices is still unclear. Thus, we focus on the function of ADAM8 in matrix remodeling and migration of 3D extracellular matrix scaffolds. Therefore, human breast carcinoma cells MDA-MB-231 with ADAM8 knocked down, referred to as ADAM8-KD cells, as well as MDA-MB-231 scrambled control cells, referred to as ADAM8-Ctrl cells, have been used to examine their ability to interact with and migrate in extracellular 3D matrices. The fiber displacements, as the capacity of cells to deform the environmental 3D matrix scaffold, has been observed. ADAM8-KD cells displace collagen fibers more strongly than ADAM8-Ctrl cells. Moreover, ADAM8-KD cells migrated more numerous in 3D collagen matrices compared to ADAM8-Ctrl cells. In fact, ADAM8 is known to degrade fibronectin in a direct and / or indirect manner. The supplementation of fibronectin before polymerization of the 3D collagen matrices caused an enhancement in fiber displacements as well as in cell invasion into fibronectin-collagen matrices of ADAM8-Ctrl cells, whereas the fiber displacements of ADAM8-KD cells did not change. However, fibrinogen and laminin supplementation induced an increase in fiber displacements of both cell types. Thus, the impact of fibronectin on selective increase in fiber displacement of ADAM8-Ctrl cells appears to be ADAM8-dependent. As a consequence, the presence of ADAM8 may provide an explanation for the longstanding controversial results of fibronectin enrichment on malignant progression of cancers such as breast cancer. Finally, ADAM8 is apparently essential for providing cell-driven fiber displacements of the extracellular matrix microenvironment, which fosters 3D motility in a fibronectin-rich environment.